2017
DOI: 10.1017/jns.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of supplementedl-carnitine for fuel efficiency, as an antioxidant, and for muscle recovery in Labrador retrievers

Abstract: The primary goal was to investigate the effects of l-carnitine on fuel efficiency, as an antioxidant, and for muscle recovery in Labrador retrievers. Dogs were split into two groups, with one group being supplemented with 250 mg/d of Carniking™ l-carnitine powder. Two experiments (Expt 1 and Expt 2) were performed over a 2-year period which included running programmes, activity monitoring, body composition scans and evaluation of recovery using biomarkers. Each experiment differed slightly in dog number and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In addition, l -carnitine supplementation has been shown to spare amino acid usage as a source of energy making them available potentially for new protein synthesis [ 51 ]. It was reported that raising dogs supplemented with l -carnitine experienced less protein degradation as a result of exercise [ 52 ]. These effects might explain the reported muscle mass increase in both animal studies and human trials [ 52 , 53 ].…”
Section: L -Carnitine and Exercisementioning
confidence: 99%
“…In addition, l -carnitine supplementation has been shown to spare amino acid usage as a source of energy making them available potentially for new protein synthesis [ 51 ]. It was reported that raising dogs supplemented with l -carnitine experienced less protein degradation as a result of exercise [ 52 ]. These effects might explain the reported muscle mass increase in both animal studies and human trials [ 52 , 53 ].…”
Section: L -Carnitine and Exercisementioning
confidence: 99%
“…This notion justifies the use of carnitine to increase muscle mass during endurance exercise. Indeed, a study conducted on dogs demonstrated that supplemented carnitine experienced less protein degradation as a result of exercise [71].…”
Section: Can Carnitine Supplementation Be Useful In Physical Exercise?mentioning
confidence: 99%
“…Moreover, carnitine supplementation, by increasing the muscle androgen receptor, may improve protein signaling, needed for recovery after exercise [70]. In addition, mitigating oxidative stress during exercise, carnitine can facilitate muscle recovery [70,71].…”
Section: Can Carnitine Supplementation Be Useful In Physical Exercise?mentioning
confidence: 99%
“…All Labrador Retrievers used in each of the described experiments were intact and ranged from 1 to 4 years of age. Muscle biopsies and serum samples were taken from 20 Labradors (10 M/10 F) for L-carnitine content quantification (EXP1) as part of a 14-week endurance exercise trial, which used 56 dogs total (Varney et al, 2017).…”
Section: Animals and Housingmentioning
confidence: 99%
“…Epp, Erickson, Woodworth, and Poole (2007) found that L-carnitine supplementation increased the potential for oxygen transport in racing greyhounds, while reducing indicators of muscle damage. Previous studies reported 125 mg L-carnitine provided daily to Labrador Retrievers produced a positive effect on activity intensity, body composition, muscle recovery and oxidative capacity during a 14-week feeding/exercise regimen (Varney, Fowler, Gilbert, & Coon, 2017).…”
Section: Introductionmentioning
confidence: 97%